PROTECTION AGAINST DETRIMENTAL EFFECTS FROM WATERS IN THE REPUBLIC OF SERBIA - Kljajić, Nataša; Popović, Vesna; Grujić, Biljana (Economics of Agriculture, 2016)
The authors of this paper emphasise the analysis of the state and investment in systems for protection against waters in the previous, transitional, period, the consequences of the 2014 floods, and fnancing the reconstruction of damaged water facilities as well as the legislative and institutional framework for the policy of protection against waters in the pre-accession period. The results of the analysis imply insuffcient investments in watercourse regulation and maintenance and improvement of facilities for protection against floods from surface water, groundwater, erosion and torrents in the transition period. In the past years, especially after the last-years floods, there is an intensifcation of activities on recovery, reconstruction and construction of water management infrastructure for protection against waters. There is also intense work on harmonising the legislation with the corresponding legislation of the EU and fulflling the obligations from the signed international conventions in this area.